Improvement of energy substrate metabolism by late evening snack supplementation in patients with liver cirrhosis: a meta-analysis - Yao J; Han W; Ren X; Yuan L; Xu J; Duan Z (Dove Medical Press, 2019)
Jia Yao,1,* Weijia Han,2,3,* Xiaojing Ren,1 Lili Yuan,1 Jun Xu,1 Zhongping Duan2,31Department of Gastroenterology and General Surgery, Shanxi Dayi Hospital, Taiyuan, People’s Republic of China; 2Difficult & Complicated Liver Diseases and Artificial Liver Center, Beijing Youan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3Beijing Municipal Key Laboratory of Liver Failure and Artificial Liver Treatment Research, Beijing, People’s Republic of China*These authors contributed equally to this work Aim: Malnutrition is one of the most common complications in patients with liver cirrhosis. Abnormal energy substrate metabolism may contribute to aggravation of malnutrition. Late evening snack (LESs) supplementation has been recommended as an intervention to reduce starvation time and improve nutritional status. Published studies have analyzed the effect of LESs on the branched-chain amino acid (BCAA)/tyrosine ratio (BTR) and oxidation rate of fat and carbohydrate in patients with liver cirrhosis.Methods: We searched PubMed, Cochrane Library, Web of Science and Embase for relevant research from January 2000 to October 2018. The primary outcome for this analysis was changes in BTR and fat and carbohydrate oxidation in patients with liver cirrhosis.Results: A total of 9 articles, containing 211 patients, were included in this analysis. The results supported that supplementation with BCAA-enriched LESs improved BTR, and long-term supplementation with BCAAs (>1 month) may be more beneficial than short-term supplementation (<1 month) in patients with liver cirrhosis. In addition, supplementation with BCAAs may increase the oxidation rate of carbohydrates and decrease the oxidation rate of fat. Furthermore, compared with liquid-enriched LESs, BCAA was a better choice for increasing the oxidation of carbohydrates and decreasing the rate of fat oxidation.Conclusion: BCAA-enriched LES supplementation is an appropriate nutritional intervention to improve abnormal energy substrate metabolism, which may improve malnutrition in patients with liver cirrhosis. Further research is needed on the long-term benefit and improved survival in patients with liver cirrhosis.Keywords: cirrhosis, late evening snack, branched-chain amino acid, energy metabolism